Ototoxicity and long-term hearing outcome in pediatric patients receiving cisplatin - Sriyapai, Tatpong; Thongyai, Kanthong; Phuakpet, Kamon; Vathana, Nassawee; Buaboonnam, Jassada; Sanpakit, Kleebsabai (The Turkish Journal of Pediatrics, 2022)
Background. Hearing is essential in child development. Cisplatin which is a common chemotherapy used in many pediatric solid-tumor protocols cause various degrees of ototoxicity. Several risk factors for cisplatininduced ototoxicity have been reported, including race and age. This study aimed to evaluate the incidence of ototoxicity and its long-term outcome in Thai pediatric solid-tumor patients receiving cisplatin and to determine the risk factors associated with hearing impairment. Methods. A retrospective study was conducted in solid-tumor patients < 15 years old from 2007 to 2019 at Siriraj Hospital, Bangkok, Thailand. Hearing was evaluated by an audiogram and/or auditory steady-state response and the impairment was graded according to the Common Terminology Criteria for Adverse Events version 5. Grade 2 and above was considered significant hearing loss. Results. In total, the hearing of 47 patients was evaluated. At the end of treatment, hearing impairment and significant hearing loss were found in 66% and 48.9% of patients, respectively. A high median cumulative cisplatin dose was significantly associated with worse hearing impairment (p = 0.039) and a more progressive grading of ototoxicity (p = 0.005). A risk factor for significant hearing loss was a cumulative dose ≥400 mg/m2 (p = 0.014). All 9 patients who received a cumulative dose > 600 mg/m2 and 5 patients who received aminoglycoside developed significant hearing loss. One patient had progressive hearing impairment at 8 months after the end of treatment and 1 patient developed grade 3 ototoxicity which required a hearing aid after bone marrow transplantation. The latter patient received a total cisplatin dose of 708.2 mg/m < sup > 2 < /sup > and carboplatin 1400 mg/m < sup > 2 < /sup > . Conclusions. The incidence of hearing impairment in pediatric patients receiving cisplatin is high. Regular hearing evaluation is essential for the early detection of ototoxicity. Long-term follow-up is recommended, especially in patients who have a combination of other risk factors for hearing loss.